Memahami Perilaku Mencari Bantuan dari Perspektif Literasi Kesehatan Mental dan Keyakinan Kesehatan Mental: Analisis - Natalia, Natalia; Theresia, Fransisca; Hardi, Nicholas (PT Kalbe Farma Tbk., 2024)
Mental disorders were prevalent worldwide, and healthcare utilization was crucial. Initiating and sustaining treatment for individuals with mental disorders was compulsory to achieve recovery, disease burden reduction, and improved quality of life. As an attempt to obtain external assistancen to cope with mental health problems, help-seeking began from the ability to perceive a need for care that raises the seeking help intention. Mental health literacy (MHL) and mental health belief (MHB) influence individuals’ awareness of mental health problems and determine their help-seeking behavior. This review aimed to comprehend help-seeking behavior promotion through MHL, MHB, and interventions known to improve them. Publications within the last 5 years from PubMed and Google Scholar were used as references, including citing the original articles. MHL was influenced by age and gender. Religion, culture, age, and gender have been identified as factors thataffect MHB. Psychoeducation is considered an essential strategy to promote help-seeking behavior, which could be performed individually or in an empowered community. Efforts to understand various populations’ MHB, enhance MHL, and encourage help-seeking behavior should be endorsed. Therefore, early intervention to prevent further mental health burdens could be conducted.